Significados de Espiritualidad de Adolescentes Adictos en Proceso de Rehabilitación Por Consumo Abusivo de Sustancias Psicoactivas. (2019)
The objective of this research is to analyze the meaning attributed to the phenomenon of spirituality by a group of adolescents with abusive use of psychoactive substances within their rehabilitation process, in the city of Bogotá. This research involved 7 teenagers from the city of Bogota who are in the process of rehabilitation between the ages of 17 and 19.